The stability phase diagram of active Brownian particles - Nie, Pin (2020)
Phase separation in a low-density gas-like phase and a high-density liquid-like one is a common trait of biological and synthetic self-propelling particle systems. The competition between motility and stochastic forces is assumed to fix the boundary between the homogeneous and the phase-separated phase. Here we demonstrate that, on the contrary, motility does also promote the homogeneous phase allowing particles to resolve their collisions. This understanding allows quantitatively predicting the spinodal line of hard self-propelling Brownian particles, the prototypical model exhibiting a motility-induced phase separation. Furthermore, we demonstrate that frictional forces control the physical process by which motility promotes the homogeneous phase. Hence, friction emerges as an experimentally variable parameter to control the motility-induced phase diagram.